Penerapan Asimilasi dan Integrasi Bagi Narapidana Perspektif Fiqih Siyasah dan Permenkumham Nomor 32 Tahun 2020 Di Lapas Kelas IIA Pekalongan - Tri Santika; Yunas Derta Luluardi (Manabia: Journal of Constitutional Law, 2021)
There is often excess capacity in detention centers. One of them is in the Class IIA Pekalongan Prison. In dealing with the spread of Covid-19 in prisons, the government makes policies in the form of assimilation and integration for prisoners to reduce the rate of Covid-19 transmissions. The formulation of the research problem (1) how is the implementation process of providing assimilation and integration during the Covid-19 pandemic at the Class IIA Pekalongan Prison? and (2) what is the perspective of fiqh siyasah regarding the provision of assimilation and integration during the Covid-19 pandemic at the Class IIA Pekalongan Prison?. This research is a field research using a qualitative approach. The result of this research is that the process of implementing assimilation and integration in the Class IIA Pekalongan detention center has been running in accordance with the Regulation of the Minister of Law and Human Rights. The application of assimilation and integration in the perspective of siyasa fiqh can be said to be not the same. Thus, the process of assimilation and integration in the Class IIA Pekalongan prison has not been fully in accordance with the instructions of Islamic law. Meanwhile, in the Permenkumham perspective, the provision of assimilation and integration in prisons is in accordance with the Minister of Law and Human Rights Regulation No. 10 and 32 of 2020.